Simultaneous Model Estimation of Turkey Pistachio Sector - Okan TEMEL; Adem AKSOY (Yüzüncü Yıl Üniversitesi Tarim Bilimleri Dergisi)
The aim of this study is to model the supply, demand, and foreign trade dimension of Pistachio between 1980 and 2018. For this purpose, the Full Information Maximum Likelihood Estimation Model (FIML) was used for estimation. In the FIML model, four different equations, namely production, consumption, import and export, which show the relationship of simultaneity, are constructed. According to the model result; In the supply model, pistachio price periodicity and time were statistically significant and coefficient signs of the variables used in the demand model were found significant and statistically significant. R2 values showing the explanation of the equations in foreign trade have been found to be quite low compared to supply and demand models. Considering the model results, accordingly, it should be directed to the production of varieties that are in demand in the world, and should be kept in front of the periodic in product incentives.